THD ANALYSIS OF LFAC TRANSMISSION SYSTEM - Amol D. Chate; Yogesh G. Bhujbal; Dr. Asha Gaikwad (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with the design of filters and THD analysis of a low-frequency ac (20Hz) transmission system. The LFAC system is interfaced with the 50Hz mainpower grid with a cycloconverter. The wind poweris collected in dc form, and is connected to the LFAC transmission line with a twelve pulse inverter. The waveformsat the sending end and receiving end of the transmission line are plotted.THD analysis of LFAC system is carried out. The circuit model of LFAC system is simulated in MATLAB/SIMULINK.